2001
DOI: 10.1023/a:1016699628402
|View full text |Cite
|
Sign up to set email alerts
|

Problem and Pathological Gambling in North American Aboriginal Populations: A Review of the Empirical Literature

Abstract: This literature review attempts to: estimate Aboriginal population prevalence rates for problem and pathological gambling and compare these rates to the general population; determine factors associated with the Aboriginal population problem gambling behaviour; and identify other salient findings and issues. Materials used in the review were drawn from available research literature and bibliographies. There were no time restrictions or study design criteria included in the review. Key words used: Aboriginal, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 10 publications
2
16
1
Order By: Relevance
“…The finding that ARPG rates among AI/AN adults were comparable to the rates of American adults is inconsistent with existing studies that found that AI/AN have disproportionately elevated rates of disordered gambling (Patterson-Silver Wolf, Welte, 2014, Volberg and Bernhard, 2006, Wardman, el-Gudebaly, 2001, Westermeyer, Canive, 2005). This finding suggests that while more problematic gambling exists in certain AI/AN communities, it is not pervasive within all AI/AN communities.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The finding that ARPG rates among AI/AN adults were comparable to the rates of American adults is inconsistent with existing studies that found that AI/AN have disproportionately elevated rates of disordered gambling (Patterson-Silver Wolf, Welte, 2014, Volberg and Bernhard, 2006, Wardman, el-Gudebaly, 2001, Westermeyer, Canive, 2005). This finding suggests that while more problematic gambling exists in certain AI/AN communities, it is not pervasive within all AI/AN communities.…”
Section: Discussioncontrasting
confidence: 79%
“…A review of the extant literature on gambling among AI/AN individuals in 2001 found PrG rates of 5.8–19% and PG rates of 6.6–22% (Wardman et al, 2001). These rates are two to five times higher than the PrG rates and four to 16 times higher than the PG rates found among non-AI/AN American adults (Wardman, el-Gudebaly, 2001). Since publication of this review, three studies have examined disordered gambling among AI/AN adults.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, however, gambling research undertaken in different first nation communities and presented at the conference, showed that although indigenous populations may have different experiences of engagement in the business of gambling and exposure to gambling related harm, in general, indigenous peoples' are two to three times at risk to developing problems with gambling than the dominant population and it is the latter population which actively promotes gambling as a legitimate business and a recreational activity. Research findings presented at this conference, unpublished, are consistent with other research that has been undertaken with first nation peoples' that gambling can become an addictive activity as a coping mechanism of the historic trauma indigenous people have experienced as well as their ongoing poverty and social and political marginalisation, (Abbott 1999;Wardman et al 2001). …”
supporting
confidence: 83%
“…In addition, the paper provides an opportunity for reflection and recognition of the importance of government administrators and tribal leaders being responsible in exercising their role and responsibility of duty of care, for those they are required to protect. Special consideration must be given for the protection of children and young people to ensure where possible current and future generations are healthy and secure in all aspects of their lives, (Wardman et al 2001). …”
mentioning
confidence: 99%
“…Some Aboriginal groups experience gambling problems three to four times higher than the general population (Volberg and Abbott 1997; Williams et al 2011). North American Aboriginal peoples are estimated to experience gambling problems at about 2–3 times higher than the general population (Belanger 2011; Wardman et al 2001). Similarly, Stevens and Young (2009b) reported a national gambling prevalence rate for Australian Aboriginal gamblers as 13.5 %.…”
mentioning
confidence: 99%